Investigating the Effect of Translanguaging on University Students’ Cognitive Load during Reading Comprehension Tasks - Roia Nahidh Hammad; Hussein Ali Ahmed (مجلة الباحث, 2026)
The study aims at investigating the pedagogical potential of planned Translanguaging (TRANS) strategies, namely the teacher-centered approach on mitigating the cognitive load (CL) imposed by monolingual instruction and fostering deeper learning through a strategic integration with Cognitive Learning Theory principles to enhance EFL university students’ performance in reading comprehension skills. To bring about this aim, a quasi-experimental design and an adapted version of Lipkin’s 2014 self-reported questionnaire have been utilized with a sample of 120 university EFL students during the academic year 2024-2025